The effect of product quality, brand image, price perception, and promotion on the purchase decision of facial wash products in the Jakarta area - Ashshiddiqi, Ardan (Journal of Entrepreneurial Economics, 2025)
Background: The skincare industry in Indonesia has been growing rapidly, resulting in intense competition among brands. Companies must therefore focus on product quality, brand image, price perception, and promotional strategies to influence consumer purchasing behavior. This study aims to analyze the effects of these four variables on purchasing decisions for Garnier facial wash products. Methods: This research used primary data collected through questionnaires distributed to 150 respondents in the Greater Jakarta area who have purchased and used Garnier facial wash. The sampling technique applied was non-probability sampling with accidental sampling. The data were analyzed using SPSS, employing validity, reliability, normality, multicollinearity, heteroscedasticity, multiple linear regression, F-test, T-test, and coefficient of determination tests. Finding: The results show that product quality, brand image, price perception, and promotion have a simultaneous and partial positive effect on purchasing decisions. Among these, product quality has the most dominant influence, indicating that consumers prioritize product effectiveness and reliability when purchasing skincare products. Conclusion: Product quality, brand image, price perception, and promotion significantly and positively affect consumer purchasing decisions for Garnier facial wash. Product quality remains the most decisive factor, suggesting that continuous improvement in quality, coupled with strong branding, fair pricing, and effective promotion, can enhance consumer purchase intentions. Novelty/Originality of this article: This study contributes empirical evidence on the relative importance of marketing mix variables—especially product quality—in influencing purchasing decisions in Indonesia’s competitive skincare market. It highlights the dominance of perceived product quality in shaping consumer choices for beauty care products.